2001
DOI: 10.4269/ajtmh.2001.64.298
|View full text |Cite
|
Sign up to set email alerts
|

Pathogenic aspects of pyogenic liver abscess associated with experimental schistosomiasis.

Abstract: Abstract. Schistosomiasis mansoni infection that occurs concurrently with Staphylococcus aureus bacteremia favors the formation of pyogenic liver abscess. The present experimental study in mice evaluated the following aspects of the relationship between infection with Schistosoma mansoni and liver abscess caused by S. aureus: a) the role of the eggs of S. mansoni in the genesis of the abscesses; b) the influence of different phases of schistosomiasis in the development of liver abscesses; and c) the effect of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
3
0

Year Published

2001
2001
2011
2011

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 22 publications
1
3
0
Order By: Relevance
“…17,18 Other investigators have reported a relationship between S. mansoni infection and pyogenic liver abscesses caused by S. aureus in experimentally infected mice and in humans. 19,20 These findings may also relate pelvic abscesses and shistosomiasis in our patient.…”
Section: Discussionsupporting
confidence: 55%
“…17,18 Other investigators have reported a relationship between S. mansoni infection and pyogenic liver abscesses caused by S. aureus in experimentally infected mice and in humans. 19,20 These findings may also relate pelvic abscesses and shistosomiasis in our patient.…”
Section: Discussionsupporting
confidence: 55%
“…The relationship of schistosomiasis and hepatic pyogenic abscess has been well documented in medical literature from clinical (Lambertucci et al 1997(Lambertucci et al , 2001) and experimental studies (Teixeira et al 2001) with Staphylococcus aureus as the main agent.…”
Section: Resultsmentioning
confidence: 99%
“…Experimental studies of some strains have shown differences regarding the quantity of eggs in the phase of oviposition, infectivity, and pathogenicity and these factors are not worm-burden dependent (Teixeira et al 2001). When different results are obtained in experimentals with S. mansoni, these discrepancies are usually attributed to difference in the parasite strain used.…”
mentioning
confidence: 93%
“…The association between pyogenic abscesses caused by Staphylococcus aureus and worm infection has been described (Lambertucci et al 1990, 2001, Teixeira et al 2001a,b, Pinilla et al 2001. Lambertucci et al (1998) and Rayes et al (2000) also found an association between tropical pyomyositis and infection by Toxocara canis.…”
mentioning
confidence: 96%